Isoflurane post-treatment improves pulmonary vascular permeability via upregulation of heme oxygenase-1. (1st September 2013) - Dong, Xiang; Hu, Rong; Sun, Yu; Li, Qifang; Jiang, Hong
ABSTRACT: Isoflurane (ISO) has been shown to attenuate acute lung injury (ALI). Induction of heme oxygenase-1 (HO-1) and suppression of inducible nitric oxide synthase (iNOS) expression provide cytoprotection in lung and vascular injury. The aim of this study was to investigate the effect of post-treatment with isoflurane on lung vascular permeability and the role of HO-1 in an ALI rat model induced by cecal ligation and puncture (CLP). Male Sprague–Dawley rats were randomly assigned to one of four groups: sham group, sham rats post-treated with vehicle (Sham); CLP group, CLP rats post-treated with vehicle (CLP); ISO group, CLP rats post-treated with isoflurane (ISO); and ZnPP group, CLP rats injected with zinc protoporphyrin IX (ZnPP), a competitive inhibitor of HO-1, 1 hour before the operation, and post-treated with isoflurane (ZnPP). Isoflurane (1.4%) was administered 2 hour after CLP. At 24 hour after CLP, the extent of ALI was evaluated by lung wet/dry ratio, Evans blue dye (EBD) extravasation, lung permeability index (LPI), as well as histological and immunohistochemical examinations. We also determined pulmonary iNOS and HO-1 expression. Compared with the CLP group, the isoflurane post-treatment group showed improved pulmonary microvascular permeability as detected by EBD extravasation, LPI, as well as histological and immunohistochemical examinations. Furthermore, isoflurane decreased iNOS and increased HO-1 expression in lung tissue. Pretreatment with ZnPP prevented the protective effects of isoflurane in rats. These findings indicate that the protective role of isoflurane post-conditioning against CLP-induced lung injury may be associated with its role in upregulating HO-1 in ALI.